Aplicações de imagens digitais e análise multivariada para classificação e determinação de parâmetros de qualidade em plumas de algodão - Gonçalves, Maria Ivanda Silva (2015)
In recent years, commercial cotton lint have been developed with better quality, presenting different characteristics, but with similar coloring. This can be a problem because these samples is identified, large-scale, performed by a visual inspection, which is a very subjective method and error prone. Another way available for classification of samples is the use of HVI system (High Volume Instruments) to determine physical quality parameters. However, this apparatus has a high cost when compared to digital imaging technique, furthermore has the need for adequate infrastructure and a trained analyst for analysis procedure. This work proposes the development of a novel analytical method based on the use of digital image and multivariate analysis to (1) naturally colored cotton plumes classification according to the type of cultivar and (2) simultaneous determination of degree of yellowness (+b), reflectance (Rd) and wax content (WAX). The acquisition of digital images of cotton lints was carried out through a webcam and histograms containing distributions in levels of colors in standard RGB (red-green-blue), grayscale and HSV system (hue-saturation-value) they were obtained. In the classification of samples, models based discriminant analysis by partial least squares (PLS-DA) and linear discriminant analysis (LDA) with variable selection by the successive projections algorithm (SPA) or stepwise (SW) were evaluated. For the determination of the parameters +b, Rd and WAX, PLS models and multiple linear regression (MLR) with variable selection by the SPA were developed and compared. The best classification results were obtained with LDA / SW model with a correct classification rate (TCC) of 96% for the test group using the HSV combination. As the calibration methods, satisfactory prediction results were obtained for both models (PLS and MLR-SPA) with values of RMSEP near repeatability of the reference method. Furthermore, no systematic error was observed and there were no significant differences between the predicted values and reference, according to a paired t-test at 95% confidence. As advantages of the method is simple, low cost, does not use reagent, does not destroy the sample and realizes analysis at short time intervals.